Handbook of Indo-Pacific Studies - Kratiuk, Barbara; Van den Bosch, Jeroen J. J.; Jaskólska, Aleksandra; Sato, Yoichiro (Indo-Pacific in Context, 2023)
This handbook explores the significance of the Indo-Pacific in world politics. It shows how the re-emergence of the Indo-Pacific in international relations has fundamentally changed the approach to politics, economics and security. The volume: explores the themes related to trade, politics and security for better understanding of the Indo-Pacific and the repercussions of the region's emergence studies different security and political issues in the region: military competition, maritime governance, strategic alliances and rivalries, and international conflicts analyses various socio-economic dimensions of the Indo-Pacific, such as political systems, cultural and religious contexts, and trade and financial systems examines the strategies of various states, such as the United States, Japan, India and China, and their approaches towards the Indo-Pacific covers the role of middle powers and small states in detail Interdisciplinary in approach and with essays from authors from around the world, this volume will be indispensable to scholars, researchers and students in the fields of international relations, politics and Asian studies.